PENGARUH SUHU DAN DURASI PENYINARAN PANEL SURYA TERHADAP EFISIENSI ENERGI PANEL SURYA: STUDI KASUS PLTS INSTITUT TEKNOLOGI PLN - Zahriya Okta Priani, Hakimul Batih, Syamsir Abduh (Integrative Perspectives of Social and Science Journal, 2025)
This study examines the effects of temperature and solar exposure duration on photovoltaic panel efficiency in tropical regions, using a case study at the PLN Institute of Technology's Solar Power Plant (PLTS) in Jakarta. The background highlights challenges in PLTS efficiency under tropical climates vulnerable to high temperatures and solar radiation fluctuations. The objective is to analyze the simultaneous impact of both factors during dry and rainy seasons. The method employs Partial Least Squares Structural Equation Modeling (PLS-SEM) with field data collected over 6 months (January-June 2025). Results reveal that temperature has a strongly significant negative effect on efficiency in both seasons (coefficient -1.128 for dry; -1.065 for rainy), while solar exposure shows smaller positive effects (0.361 for dry; 0.209 for rainy). A key finding is the dominant role of temperature regardless of season, whereas solar radiation remains significant even at low intensity. The study implies the need for panel cooling systems and climate-specific adaptation strategies to optimize PLTS in tropical areas.